Minimally Invasive Surgery for Clinical Crown Lengthening Using Piezoelectric Ultrasound - Marcantonio, Ana Carolina Monachini [UNESP]; De Oliveira, Guilherme José Pimentel Lopes; Scardueli, Cássio Rocha [UNESP]; Marcantonio, Camila Chiérici [UNESP]; Marcantonio, Rosemary Adriana Chiérici [UNESP]; Marcantonio, Elcio [UNESP] (Wiley, 2020)
This case report is aimed at describing a flapless, minimally invasive clinical crown lengthening with an osteotomy performed using a piezoelectric ultrasound. A female patient complained about the amount of gum that was exposed when she smiled, which caused aesthetic discomfort. After a clinical examination, it was confirmed that the patient had excessive gum exposure in the upper arch of the dental region for teeth 14 to 24 when she smiled. The tomographic exam showed that bone tissue was at the level of the enamel-cementum junction, and gingival tissue covered a part of the anatomic crown. Virtual analysis using digital smile design (DSD) demonstrated that enlarging the clinical crowns would provide better aesthetics. The excess gingival tissue was removed from the gingival margin region with the aid of a mockup without interference to the interdental papillae. Then, osteotomy was performed using piezoelectric ultrasound until there was a 2.5 mm distance from the top of the bone crest to the new gingival margin. In the postoperative period, good repositioning of the gingival margin, absence of postoperative complications, and rapid healing of the gingival tissue were verified. After 6 months, a good aesthetic outcome was observed with stability in the level of the periodontal tissues obtained via the crown-lengthening technique. It can be concluded that the minimally invasive clinical crown-lengthening technique was effective in repositioning the gingival margin with no postoperative complications.